Tanggung Jawab Hukum Warga Negara dalam Mengatasi Kejahatan Cyber dan Mendorong Stabilitas Sosial - Amalia Zahra (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2025)
Cyber crimes are crimes that are based on the internet and digital devices. Data theft, hacking, and widespread online fraud are a few examples of these crimes. To overcome this, the legal responsibility of the state is very important in overcoming this illegal activity through compliance with regulations and active participation of citizens to report if there are illegal or suspicious activities. In the context of Sustainable Development Goal 16, which emphasizes peace and justice for all, cooperation between governments, law enforcement and communities is needed to create peace in the social and also digital spheres.